Job-demand and family business resources in pandemic context: How they influence burnout and job satisfaction - Llanos-Contreras, Orlando; Ibáñez, María José; Prado-Gascó, Vicente Javier (Frontiers in Psychology, 2023)
This research aims to explore how work demands and resource variables affect the burnout and satisfaction of employees of family businesses in the context of the pandemic (Covid-19) and the moderation effect of fear of Covid-19 on this relationship. A sample of 214 Chilean family business employees is used for hypotheses testing. Results indicate that the demands and resources partially explain the burnout and satisfaction of employees of family firms during the pandemic. Employees’ fear of Covid-19 moderates the relationship between resources-demands and burnout-job satisfaction in family firms. This work contributes to understanding how these organizations can manage adverse scenarios to survive and continue operations.